Moderation of Self-Control on The Relationship of Financial Literacy and Saving Behavior in Women - Lupikawaty, Marieska; Fadila, Dewi; Zainal Ridho, Sari Lestari; Angguna, Welan Mauli; Nurcahaya, Claudia; Fadhil, Sayyid Muhammad (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study aimed to examine savings behavior of 97 women in the millennial generation and Gen Z group who live in rural areas. Recent surveys show that millennials and Gen Z recognize the importance of saving but only have savings that are enough to fulfill their life for three months. The research was conducted using a quantitative experimental between subject design method to answer questions regarding the influence of financial knowledge socialization on financial literacy. A non-experimental quantitative study was conducted to determine the moderating role of self-control on the influence of financial literacy on saving behavior through self-report on valid and reliable questionnaires and scales. The study results show that financial literacy and self-control have a role in explaining saving behavior (R2 = 0.52, p ≤ 0.05). Financial literacy has a significant positive impact in increasing saving behavior. Self-control also has an equally significant influence in explaining saving behavior. However, through testing the moderating role, self-control has a significant negative impact in influencing the relationship between financial literacy and saving behavior, this is interesting for further discussion.